(untitled) (Medical Forum Monthly, 2024)
Background: Thrombolytic therapy for Acute Myocardial Infarction has been one of the most potent treatment ever developed for condition that kill more patients worldwide than any other. Objective: To evaluate the benefit and efficacy or observational studies of streptokinase therapy on ST-segment elevation resolution in different types of myocardial infarction that focus especially on the younger age group less than forty years. Study design: To observe the streptokinase therapy, in ST-segment elevation resolution, in age less than 40 years and in different types of myocardial infarction. Place and Duration of Study: The study was conducted at national institute of cardiovascular diseases (NICVD) of Pakistan, Karachi. Materials and Methods: All patients fulfilling the inclusion criteria for thrombolytic therapy were included. Baseline ECG recorded before streptokinase infusion and repeated at completion of infusion i.e. 90 minutes, day 1 and day 2. Results: Streptokinase therapy on blood pressure, CKMB, and ST-segment resolution at 90 minutes, day 1, and Day2 in less than 40-year of age patient. The mean systolic blood pressure was 124+ 3.32 and 112+3.00 pre and post SK therapy reflecting a percentage decrease of 6.67 and highly significant (P<0.001). The Diastolic blood pressure was decrease to 6.25% with a mean value of 76.80+ 2.70 and 72+1.91 before and after the Streptokinase therapy’s, segment resolution at 90 minutes was decreased to 52.01 percent from the baseline and continued to decrease at Day-1 and Day-2 with a percentage reduction of 70.65 and 83.69 % respectively. The P values were highly significant (P<0.001). Conclusion: Thrombolysis improves survival when given within 12 hours of the onset of symptoms. The magnitude of benefit is greatest when reperfusion is established early. Age itself should not be considered a contraindication for fibronolysis